Glucose-6-phosphate dehydrogenase activity of Neurospora grown on media containing malonate and citrate - P. T. Cheng; J. E. Willis (Fungal Genetics Reports, 1966)
Glucose-6-phosphate dehydrogenase activity om malonate and citrate